The Secular religion of life – philosophical perspective = Świecka religia życia – perspektywa filozoficzna - Guzowska, Beata (Przegla̜d religioznawczy, 2020)
Modern communities in their spiritual and religious search often tend to forsake the values presented by traditional Churches, choosing other, proposed by diverse religious and secular sources. Today’s philosophical conceptual grid is open for the changes geared inter alia to blurring the boundaries between what is private and what is public, everyday and festive, aesthetic and unaesthetic. Modern culture changes cause humans to see life as the most important value - it’s fullness and the ways of living it. That recognition of life’s absolute value has come to be on the way of overcoming the religion. One’s decisions about life’s shape are made due to increasing amount of factors, and man alone can "construct himself" from many different elements available on the idea market with values are attractive to him, having freedom of choice, belief and lifestyle.